Timer/Generator Circuits Manual - M., R. Marston (Newnes, 2013)
Timer/Generator Circuits Manual is an 11-chapter text that deals mainly with waveform generator techniques and circuits. Each chapter starts with an explanation of the basic principles of its subject followed by a wide range of practical circuit designs. This work presents a total of over 300 practical circuits, diagrams, and tables. Chapter 1 outlines the basic principles and the different types of generator. Chapters 2 to 9 deal with a specific type of waveform generator, including sine, square, triangular, sawtooth, and special waveform generators pulse. These chapters also include pulse generator, time IC generator, and waveform synthesizer circuits. Chapter 10 examines the characteristics of phase-locked loop circuits, while Chapter 11 looks into the miscellaneous applications of the ubiquitous "555" timer type of integrated circuit. The appendix presents a number of useful waveform generator design charts, as an aid to those readers who wish to design or modify generator circuits to their own specifications. This book will prove useful to practical design engineers, technicians, experimenters, and electronics students.